Poultices Generated Mechanically with Compressed Air: “Gunpoint Mix System” Characterization and Properties. Comparison with “Handmade” Poultices (Global Journal of Human-Social Science, 2023)
The authors have developed an automated method Gunpoint mix hQps youtu be 4uXC_OoP7EM for the manufacture of poultrices The proper es of the cellulose poultrices placed manually with those placed with the GunPoint Mix method applied on stone substrates of known characteris cs are compared Arbocel BWW40 is used in both cases The physical parameters of the cellulose the microscopic texture the absorp on and desorp on proper es the penetra on of a consolida ng product and the ease of cleaning are measured The main advantage of the Gunpoint mix method lies in the speed of the applica on that allows a very exact control of the applica on mes Given its good adhesion it can be applied with the same speed in the roof and top of the vaults upside down without the risk of landslides The water parameters of each type of poultrice provide informa on to the restorer to decide on what type of treatment is more appropriate to use a handmade poultrice or a Gunpoint mix poultrice
Keywords: paper pulp; poultrice; gunpoint mix; comparative; physical parameters; operability; hand-setting